Atomic Layer Deposition on Block Copolymer Membranes with Gyroidal Nanopores Toward Periodically Nanostructured Vapor Sensors: Nanotubes versus Nanorods. Issue 16 (10th May 2016) - Guo, Leiming; Zhong, Zhaoxiang; Wang, Yong
Abstract : 3D gyroidal networks of ZnO nanorods or nanotubes are synthesized by replicating block copolymer (BCP) templates with gyroidal nanopores via atomic layer deposition (ALD). The generation of 3D ZnO nanorods or nanotubes depends on the thicknesses of deposited ZnO layers, which can be easily and precisely controlled by adjusting ALD cycles. The as‐obtained ZnO nanostructures have porosities as high as 77% for gyroidal nanorods and 86% for gyroidal nanotubes due to their unique interconnected structures and rough surfaces. Both gyroidal ZnO nanostructures are used as vapor sensors to detect ethanol with different concentrations. Gyroidal ZnO nanotubes show higher ethanol sensitivity than nanorods because of the inherently interconnected nanotubes and larger porosity. Gyroidal ZnO nanotubes can also act as formaldehyde sensors with the sensitivity as high as 42 to 50 ppm formaldehyde, which is much higher than previously reported sensors based on ZnO nanorods or nanotubes. Abstract : Atomic layer deposition (ALD) on block copolymer templates with gyroidal nanopores followed by calcining, producing periodical networks composed of ZnO 1D nanostructures . By modulating the ALD cycle number, the ZnO nanorods or nanotubes can be flexibly tuned. Both nanorods and nanotubes show good sensitivity toward ethanol vapor, and the tubes work even better than rods for their hollow interiors. The ZnO networks of nanotubes exhibit much higher sensitivity to formaldehyde than previously reported ZnO nanorods or nanotubes.